The Role of the Werkudara Double-Decker Tourist Bus in Strengthening the Tourism Identity of Solo City - wulan, Ajeng Ayu Wulandari; Fahrudin, Atef (Universitas Pendidikan Nasional, 2024)
This study analyzes the role of the Werkudara Double-Decker Tourist Bus in strengthening the tourism identity of Solo City using the Stimulus-Organism-Response (S-O-R) theory. With its distinctive design reflecting local culture and educational narratives delivered by tour guides, the bus serves as a unique mode of tourist transportation in Solo. Through in-depth interviews with five respondents, including tourists, the study reveals that the bus’s visual and narrative stimuli positively impact tourists’ perceptions of Solo. The striking design and rich cultural storytelling enhance appreciation for the city’s history and local culture, thereby reinforcing Solo’s image as a cultural tourism destination. As a result, these stimuli elicit positive responses, such as increased interest in visiting other attractions in Solo and a willingness to recommend the city to others. Through its visual and narrative elements, the Werkudara Bus plays a significant role in strengthening Solo’s tourism identity